Errores que no pudimos corregir - CARRERA, Elena F.de; BERGESIO, Nélida de; ARRALDE, Zulma; TABORDA, Liliana (UNION MATEMATICA ARGENTINA, 2003)
Docentes de la Facultad de Bioquímica y Cs.Biológicas de la U.N.L.